Electrochemical and XPS investigations on the galvanic interaction between pentlandite and pyrrhotite in collectorless flotation system. (December 2022) - Liu, Dezhi; Zhang, Guofan; Li, BinBin
Graphical abstract: In the galvanic couple of pentlandite/pyrrhotite, pentlandite acted as the cathode, while pyrrhotite acted as the anode. The oxidation and metal dissolution of pyrrhotite was accelerated, but the H + generated in anodic reaction against forming oxide film on its surface. However, the production of OH – caused the thickening of oxide film on the pentlandite surface. Galvanic interaction between pentlandite and pyrrhotite significantly affected their flotation, which was also impacted by their relative content ratio. Highlights: Galvanic interaction of pentlandite and pyrrhotite was rarely investigated. The increase of OH – on cathode caused the thickening of oxide film on pentlandite. The H + generated in anodic reaction against forming oxide film on pyrrhotite. Galvanic interaction greatly affected their surface properties and floatability. Abstract: Pentlandite and pyrrhotite are ubiquitously symbiotically aggregated with each other, and the galvanic interaction between them inevitably occurs in flotation process. However, there were few detailed researches regarding this galvanic interaction and its effect on the surface oxidation of pentlandite and pyrrhotite that has been reported. In this work, the galvanic interactions and its influence on the surface oxidation and collectorless flotation behaviors of pentlandite and pyrrhotite were systematically researched at pH 8.5. Results of electrochemical measurements showed that pentlandite had a higher OCP value than pyrrhotite, indicating that pentlandite would act as the cathode, while pyrrhotite acted as the anode in the galvanic couple. Compared to the minerals oxidized solely, a more passivated surface was found for both pentlandite and pyrrhotite. ICP-OES and XPS analyses demonstrated that in the presence of pyrrhotite, a thicker iron oxide/hydroxide film was obtained with a decrease in the species of sulfate and nickel oxide/hydroxide on pentlandite surface. For pyrrhotite, within the galvanic interaction, the oxidation and metal dissolution of pyrrhotite was accelerated. However, the hydrogen ion generated in the anodic reaction would hinder the precipitation of iron oxide/hydroxide and sulfate on pyrrhotite surface. Micro-flotation results further confirmed that the galvanic interaction between pentlandite and pyrrhotite significantly affected their collectorless flotation behaviors, which was also affected by the relative content ratio between them. This work systematically studied the galvanic interaction and its role in the surface oxidation in pentlandite/pyrrhotite collectorless flotation system, which could also provide reference for the further study on complex Ni-bearing sulfide minerals flotation.